Potassium Nutrition on Vivipary and seed quality in Oriental pickling Melon (Cucumis melo var. conomon Mak.) - Athulya S Kumar (Department of Seed Science and Technology, College of Horticulture, 2019)
Oriental pickling melon ( is an important vegetable crop cultivated in Kerala. This short duration crop has the potential to produce high yields with low input requirements, so often referred as unique vegetable of Kerala. Quality seed production in melon is affected due to the occurrence of vivipary. A study in oriental pickling melon varieties, Saubhagya and Mudicode was conducted in the Department of Seed Science and Technology, College of Horticulture, Vellanikkara, Thrissur, during 2017-2019 to elucidate the effect of potassium nutrition on vivipary and seed quality. The objective of the study was to assess the effect of time of planting and potassium application on vivipary and their effect on seed quality. The effect of time of planting on vivipary was assessed with three different time of planting i.e., December, January and February following a factorial randomized design with four replications. The fruit and seed yield attributes were found to be significantly influenced by varieties, time of planting and their interaction. Variety Mudicode was superior in parameters like fruit weight, fruit yield and female flower emergence was early in the crop sown in December. However, the presence of viviparous seeds and chaffy seed percentage were observed to be high in December planted crop. The potassium content in fruit flesh and placenta was found to be highest in the crop sown during February with minimum percentage of viviparous and chaffy seeds. The results point out that December planting is advantageous for fruit yield while February planting is advantageous for seed production in variety Mudicode. The interaction between varieties and time of planting on seed quality indices pointed out that it is advantageous to go for February time of planting for variety Mudicode for seed production. In order to study the effect of potassium on vivipary a crop was raised in February 2018 following a factorial randomised design with six treatments and three replications. During the experiment, fruit and seed quality parameters were found to be significantly influenced by varieties, fertilizer levels and their interaction. Variety Mudicode exhibited high fruit yield attributes, fresh and dry weight of seeds and 100 seed weight whereas seeds per fruit, seed yield was superior in Saubhagya with low percentage of viviparous seeds. Irrespective of varieties, treatments with additional potassium application i.e., POP + 25% K, POP + 50% K, and POP + foliar spray recorded high fruit and seed yield. Organic nutrient management also resulted in seed yield of 7.48 kg ha-1. High potassium content in fruit placenta and fruit flesh was found in treatments which exhibit least percentage of viviparous and chaffy seeds i.e., POP + foliar spray and POP + 50% K. Additional potassium application was found to be advantageous for reducing the occurrence of viviparous seeds by increasing the K content in fruit placenta and flesh. The interaction between varieties and fertilizer levels on fruit and seed parameters pointed out that additional potassium nutrition was advantageous for fruit and seed yield production of Mudicode whereas fruit weight, seeds per fruit, seed yield and occurrence of viviparous seeds and chaffy seed percentage was the least among the treatment combination of variety Saubhagya with POP + foliar spray. The seed quality during storage was evaluated following a factorial completely randomized design with the seeds collected from Experiment-II (six treatments and two replications). The seeds were dried to less than 8 per cent moisture and packed in polyethylene covers of 700G and stored under ambient conditions for a period of six months. The seed quality parameters were recorded at monthly intervals. The seed moisture and seed micro flora per cent were recorded at the start and end of the storage. Seed longevity was found to be significantly vary between varieties, fertilizer levels, and their interaction throughout the storage period. Germination, vigour indices I and II, decreased progressively over the storage period. However, towards the end of storage period, there was an increase in mean time to germination, time taken for 50 per cent germination, electrical conductivity of seed leachate, seed micro flora per cent. Irrespective of the varieties, fertilizer levels and their interaction, germination percentage of 60 per cent was retained even after six months. The study revealed that that the seeds can be stored for 6 months under the ambient conditions.